2012
DOI: 10.1037/a0027719
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between mothers' and fathers' sense of competence and children's externalizing problems: The mediating role of parenting.

Abstract: This longitudinal study examined the bidirectional associations between parents' sense of competence and children's externalizing problems, mediation of these associations by parenting behaviors, and differences between mothers and fathers concerning these associations. A sample of 551 families with children (49.9% girls; mean age = 7.83 years, SD = 1.08) participated. We found children's externalizing problems to predict parents' sense of competence 6 years later, both directly and, for mothers but not for fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
2
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 52 publications
12
64
2
10
Order By: Relevance
“…The transactional model was tested among 117 young children at ages 4, 5 and 6 who had been clinically referred for EB and among three groups of caregiver: mothers, fathers and teachers. In accordance with previous findings, EB was expected to be associated with lower caregiver-child QR in the three dyads (Daley et al, 2005;Meunier et al, 2011;Slagt et al, 2012). The involvement of the three caregivers made it possible to test the validity of the transactional model in three different interactional systems.…”
Section: The Current Studysupporting
confidence: 50%
See 2 more Smart Citations
“…The transactional model was tested among 117 young children at ages 4, 5 and 6 who had been clinically referred for EB and among three groups of caregiver: mothers, fathers and teachers. In accordance with previous findings, EB was expected to be associated with lower caregiver-child QR in the three dyads (Daley et al, 2005;Meunier et al, 2011;Slagt et al, 2012). The involvement of the three caregivers made it possible to test the validity of the transactional model in three different interactional systems.…”
Section: The Current Studysupporting
confidence: 50%
“…At the same time, EB is thought to be more likely to emerge or persist when caregivers resort to criticism, controlling or harsh discipline that in turn reinforces children's problematic behavior (Dishion, French, & Patterson, 1995;Patterson, DeBaryshe, & Ramsey, 1989;Slagt et al, 2012;Snyder, Reid, & Patterson, 2003). It has therefore been suggested that negative transactions account for the development of EB.…”
Section: The Transactional Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental efficacy is defined as one's estimation of one's ability to be a competent and successful parent (Coleman & Karraker, 2003). It is a focal component of parenting and is connected to a general sense of self-efficacy and positive affect (Coleman & Karraker, 2003) as well as to supportive parenting and limited use of inefficient disciplinary means (Slagt, Deković, De Haan, Van den Akker, & Prinzie, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This was the only process that was tested. The second study (Slagt, Deković, de Haan, van den Akker, & Prinzie, 2012) included mothers and fathers and their children followed from pre-adolescence to adolescence (6 to 10 years old at T1). The authors tested a PSE-driven process where PSE predicted changes in children's externalizing directly (PSEchild behaviors) or via supportive parenting and inept discipline (PSEparentingchild behaviors).…”
Section: Children's Behaviormentioning
confidence: 99%